“Working in the content factory”: musicians’ social media use and mental health as seen through the lens of a transdiagnostic cognitive behavioural conceptualisation - Musgrave, George; Carney, Daniel; Silver, Emma; Tibber, Marc S. (Frontiers in Psychology, 2025)
Research shows that musicians are an at-risk occupational group for mental health difficulties and suicidality. Further, social media has become central to working musicians’ lives, and there is a growing concern that social media may be linked to the increasing prevalence of mental health difficulties within the general population. Despite this, few studies have explored the role of social media in musicians’ mental health and wellbeing, both in terms of benefits to harness, as well as harms to avoid. Drawing on a transdiagnostic cognitive behavioural conceptualisation of social media use and mental health links, this interdisciplinary qualitative article draws on semi-structured interviews with twelve musicians from across the United Kingdom building careers in genres of popular, i.e., non-classical, music. Findings from thematic analysis highlighted potential benefits and harms of social media engagement, e.g., opportunities for social connection, self-expression, networking, career building, and as a source of inspiration, as well as the possibility of social disconnection, harmful social comparisons, experiences of stigma, trolling and abuse, uncertainty around the nature of the algorithm, and a sense of needing to share more and more, with a risk that it starts to displace valued offline activities. We explore these findings through the lens of a transdiagnostic conceptualisation, and highlight clinical implications aimed at supporting musicians to use social media in ways that support their wellbeing.